Differential efficiency in exogenous DNA acquisition among closely related Salmonella strains: implications in bacterial speciation - Bao, Hong-Xia (BioMed Central, 2014)
BACKGROUND: Acquisition of exogenous genetic material is a key event in bacterial speciation. It seems reasonable to assume that recombination of the incoming DNA into genome would be more efficient with higher levels of relatedness between the DNA donor and recipient. If so, bacterial speciation would be a smooth process, leading to a continuous spectrum of genomic divergence of bacteria, which, however, is not the case as shown by recent findings. The goal of this study was todetermine if DNA transfer efficiency is correlated with the levels of sequence identity. RESULTS: To compare the relative efficiency of exogenous DNA acquisition among closely related bacteria, we carried out phage-mediated transduction and plasmid-mediated transformation in representative Salmonella strains with different levels of relatedness. We found that the efficiency was remarkably variable even among genetically almost identical bacteria. Although there was a general tendency that more closely related DNA donor-recipient pairs had higher transduction efficiency, transformation efficiency exhibited over a thousand times difference among the closely related Salmonella strains. CONCLUSION: DNA acquisition efficiency is greatly variable among bacteria that have as high as over 99% identical genetic background, suggesting that bacterial speciation involves highly complex processes affected not only by whether beneficial exogenous DNA may exist in the environment but also the “readiness” of the bacteria to accept it.